Development journey and outlook of Chinese giant oilfields - Mikael Höök; Tang Xu; Pang Xiongqi; Kjell Aleklett (Petroleum Exploration and Development, 2010)
Over 70% of China's domestic oil production is obtained from 9 giant oilfields. Understanding the behaviour of these fields is essential to both domestic oil production and future Chinese oil imports. This study utilizes decline curves and depletion rate analysis to create some future production outlooks for the Chinese giant oilfields. We can conclude that China's future domestic oil production faces a significant challenge caused by maturing and declining giant fields. Evidence also indicates that the extensive use of water flooding and enhanced oil recovery methods may be masking increasing scarcity and may result in even steeper future decline rates than the ones currently being seen. The Chinese petroleum industry has managed to keep many of their giants on a production plateau for many decades. However, nothing can change the eventual onset of decline in oilfields and many of the Chinese giants have already passed their peak production levels. Our results suggest that a considerable drop in oil production from the Chinese giant oilfields can be expected over the next decades. 摘要: 中国国内超过70%的原油产量来自于9个大油田。掌握这些油田的动态对于了解中国国内原油产量和未来中国原油进口需求是必要的。该研究利用递减曲线和采油速度分析，得出中国大油田未来产量的走势。研究表明，中国国内未来原油产量将会面临一个巨大的挑战，而这正是由大油田的成熟和递减引起的。证据也表明，水驱和提高采收率方法的大规模运用将会掩盖日益严重的资源缺乏，并可能会导致油田未来递减率比目前所见到的递减率更大。中国石油工业已经设法使其国内大油田的产量在几十年内保持稳定，但任何措施都无法阻止这些油田最终走向递减，且中国许多大油田已经过了峰值产量期进入递减。笔者认为，在未来几十年里，中国大油田的原油产量将大幅降低。 Key words: giant oilfields, future Chinese oil production, decline curve analysis, production modelling, oil production strategy